The fig leaves (Ficus carica L.) on blood sugar and cholesterol levels in patients with diabetes mellitus - Bahjatun Nadrati; Elisa Oktaviana; Zuliardi Zuliardi; Lalu Dedy Supriatna; Zurriyatun Toyyibah; Raden Ahmad Dedy Mardani (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Diabetes Mellitus in Indonesia was ranked the 6th highest in the world in 2017. In NTB, the prevalence of DM increased to 1.5% per year and became top 10 most diseases in NTB Province. One of the non-pharmacological approaches that can be used by DM patients with high blood sugar and high cholesterol is herbal therapy of Fig Leaves (ficus carica) steeping water. Fig leaves are rich in flavonoids and pectin which are able to control blood sugar and cholesterol metabolism in the body, relax blood vessels and prevent the establishment of atherosclerosis. Pectin triggers bile secretion in digestive tract which binds cholesterol and excretes it out of the body with feces.Purpose: Knowing the Effect of fig leaves (Ficus carica L.) on blood sugar and cholesterol levels  in  patients with diabetes mellitusMethod: A quasi-experimental study with descriptive analytic design and pre and post-test of non-equivalent control group design. Sampling used the purposive sampling technique and obtained 30 participants divided into 2 groups. 15 participants in the intervention group and 15 participants in the control group. The research instruments were questionnaires on characteristics, observation sheets. Data analysis used the Pairet t-test.Results: In the intervention group, the statistical test results showed that there was a significant difference between blood sugar levels before and after intervention (p-value 0.000) and a significant difference between total cholesterol before and after intervention (p-value 0.000).Conclusion : There is an effect of the fig leaves (Ficus carica L.) on blood sugar and cholesterol levels in  patients with diabetes mellitus